Effect of glycerol monostearate on the structure and retrogradation of gelatinized wheat starch at high temperature - Qi Xu; Shangyuan Sang; Yanli Wang; Chin Ping Tan; Lukasz Peplowski; Xiaojuan Tang; Man Meng; Hongtao Lei (Grain & Oil Science and Technology)
Starch retrogradation is a primary contributor to the staling of bread. The impact of the surfactant glyceryl monostearate (GMS) on the structure and retrogradation characteristics of wheat starch gels was explored during storage at 4 °C for 2 h and 5 d. In this research, the incorporation of GMS (0.14 %, W/W, based on flour weight) significantly reduced the crumb firmness (P < 0.05). Molecular dynamics simulation vividly demonstrated the formation process of the single-helical amylose-GMS complex within 150 ns during the short-term retrogradation process of cooling the gelatinized starch for 2 h. X-ray diffraction analysis revealed that GMS slightly decreased the relative crystallinity of starch from 8.9 % to 7.8 % during long-term retrogradation. The reduction in R1047/1022 detected by Fourier-transform infrared spectroscopy indicated that GMS could reduce the degree of retrogradation. Solid-state 13C NMR analysis showed a characteristic resonance peak at 31.7 ppm for the GMS-starch complex. This study indicates that GMS holds great application potential in retarding starch retrogradation.